Two new species and additional records of the genus Lathrobium Gravenhorst (Coleoptera: Staphylinidae: Paederinae) from the Huaping Natural Reserve, Guangxi, southern China - Peng, Zhong; Tang, Shi-Chao (Zootaxa, 2024)
Material of the paederine genus Lathrobium Gravenhorst, 1802 from the Huaping Natural Reserve, southern China, is examined. Three species are identified, one of them described previously and two undescribed. Two species are described and illustrated for the first time, all of them micropterous: L. duanfeiyui Peng &Tang, sp. nov. and L. huapingense Peng &Tang, sp. nov. Including the new taxa, 229 Lathrobium species are currently known from mainland China.